The influence of fluorinated MWCNT distribution quality on the mechanical properties of the bulk oriented UHMWPE-based composites - A.V. Maksimkin; K.S. Mostovaya; F.S. Senatov; D.I. Chukov; S.G. Nematulloev; L.K. Olifirov (Results in Physics, 2017)
The bulk oriented UHMWPE-based composites were obtained. Fluorinated carbon nanotubes were used as a reinforcing filler. The filler contributes in the formation of nanofibrillar supramolecular structure, that in its turn acts as the harder phase in the nanocomposites synthesized. The influence of the quality of the carbon nanotubes distribution on the mechanical properties under tension was shown.